The Fiesta of the Carnival in Evaristo Valle’s Pictorical Work - Vallina Vallina, Alicia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2014)
The work of the Asturian artist Evaristo Valle is riddled with anthropologic linked references, in many cases, to the pagan festivity of the carnival. This one sinks his roots in the classic mythology, though he has been accompanying the man throughout the centuries in his innumerable artistic manifestations. In the following article there are demonstrated the classic origins of the holiday of the carnival and the work of the gijonés is analyzed in the light of the principal characteristics of a festivity that wakes up the original senses of the man and his irrational nature.